Payroll Tax and Welfare - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2008)
This paper takes a general equilibrium approach to payroll taxation. The focus of the study will be to estimate the welfare costs due to that distortionary policy.
Keywords: A1; 330; payroll tax; welfare